Fine Mapping of Inhibitory Anti-factor V Antibodies Using Factor V C2 Domain Mutants - Izumi, Tomonori; Kim, Suhng Wook; Greist, Anne; Macedo-Ribeiro, Sandra; Fuentes-Prior, Pablo; Bode, Wolfram; Kane, William H.; Ortel, Thomas L. (Thrombosis and Haemostasis, 2001)
Hemorrhagic factor V inhibitors frequently bind to the second C-type (C2) domain of factor V and interfere with phospholipid binding. To define specific residues recognized by inhibitors from four patients (one bovine thrombin-induced and three spontaneous antibodies), epitope mapping was performed using recombinant human factor V lacking most of the B-type domain (FV des B) and alanine-substituted mutants within the C2 domain (FV des B C2 mutants). FV des B C2 mutants located in the region between Lys2060 and Glu2069 were resistant to inhibition by three IgG preparations including the bovine thrombin-induced antibody in both prothrombinase and phospholipid-binding assays. In contrast, mutations at Lys2087 and Lys2092/ Glu2096 were significantly resistant to inhibition by the fourth IgG preparation in both prothrombinase and phospholipid-binding assays. These results confirm interference of phospholipid binding by hemorrhagic factor V inhibitors and support the role(s) of these residues in phospholipid binding.Presented in part at the 41st Annual Meeting of the American Society of Hematology, New Orleans, Louisiana, December 3–7, 1999
Keywords: Factor V; hemorrhagic inhibitor; epitope mapping; C2 domain; phospholipid binding